2019
DOI: 10.1016/j.advwatres.2019.103378
|View full text |Cite
|
Sign up to set email alerts
|

Pore-network modelling of non-Darcy flow through heterogeneous porous media

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 75 publications
3
24
0
Order By: Relevance
“…This spatial variation can notably be dependent on the capillary forces and the viscous dissipation in the interfaces [74] and on the pore morphology of the rock [75]. For Estaillades rock, it was shown that the medium heterogeneity creates stagnant zones with low-pressure values next to zones with high-pressure values, which results in considerable variation in the velocity distribution [76]. This could have largely affected the sweep efficiency and oil recovery in our experiments (Figure 4).…”
Section: Comparison With Pore-scale Network and Importance Of Length ...mentioning
confidence: 82%
“…This spatial variation can notably be dependent on the capillary forces and the viscous dissipation in the interfaces [74] and on the pore morphology of the rock [75]. For Estaillades rock, it was shown that the medium heterogeneity creates stagnant zones with low-pressure values next to zones with high-pressure values, which results in considerable variation in the velocity distribution [76]. This could have largely affected the sweep efficiency and oil recovery in our experiments (Figure 4).…”
Section: Comparison With Pore-scale Network and Importance Of Length ...mentioning
confidence: 82%
“…The differences between these algorithms are based on different pore space characterization and pore size assignment methods. The output pore network is then used to conduct flow simulations and to investigate different processes such as wettability, multiphase flow, reactive transport, and no-Darcy flow [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, several experimental evidences through multiple porous packing suggest the development of non-Darcy Cow condition (nonlinear Bltration) in higher Cow velocities, where the Darcy's linear model is not sufBcient to describe the Cow. It can be considered that such situations occur when the inertial drag exceeds 1% of the total pressure loss; resulting a non-linear behaviour between the pressure gradient and the superBcial velocity (El-Zehairy et al 2019). However, two of the very fundamental questions regarding the nonlinear Bltration through porous packing remains largely unanswered till date.…”
Section: Introductionmentioning
confidence: 99%